THE IMPORTANCE OF DRINKING WATER FOR STUDENTS’ BODY HEALTH - Lestari, Wanda Cici; Pranata, Rio (Hanoman Journal: Physical Education and Sport, 2024)
This research aims to analyze people's understanding and attitudes towards the importance of drinking water in maintaining health. The aim of this research is to determine the public's understanding of the importance of drinking water for the health of students' bodies. The method used is descriptive quantitative with a survey approach, data collected through questionnaires is then distributed online to 40 respondents. The results of the analysis show that all respondents have a good understanding of the positive impact of water, with 100% of respondents agreeing that lack of water can cause dehydration. As many as 75% of respondents think that children need to consume more water than adults, while 95% believe that not all drinks are as good as water. Apart from that, 97.5% of respondents admitted that consuming enough water can improve concentration and maintain the function of body organs. Although awareness about the importance of water is quite good, further guidance needs to be carried out to ensure healthy water consumption habits, especially among teenagers and children. It is hoped that this research can increase public awareness of the importance of consuming enough water in everyday life.